Utility of Acoustical Detection of Coptotermes formosanus (Isoptera: Rhinotermitidae) - Weste Osbrink; Mary Cornelius (Sociobiology)
The AED 2000 and 2010 are extremely sensitive listening devices which can effectively detect and monitor termite activity through a wave guide (e.g. bolt) both qualitatively and quantitatively.  Experiments conducted with one to ten thousand termites from differing colonies infesting wood in buckets demonstrated that acoustical emission detector readings significantly increased when number of termites increased.  Termites were also detected in infested trees with the installation of several wave guides into their trunks.  These devices can detect termites and changes in termite activity caused by changes in termite numbers, making it an effective pest management professional and research tool for finding and evaluating termite infestations and efficacy of treatments in specific locations.